Working Alone Together: Coordination in Collaboration across Domains of Expertise - Bruns, Hille C. (Academy of Management Journal, 2013)
This study develops theory on how coordination occurs in collaboration across multiple expert domains. Ethnographic fieldwork at two top U.S. universities explored the emerging field of systems biology cancer research, an extreme case of cross-functional work. Scientists make diverse contributions compatible by engaging in the coordination practices of joint assessment and consultation and in the collaborative practices of counterprojection and alignment. The study advances a process model of coordination as an ensemble of different types of practices that drive collaboration across domains. Insights into how experts coordinate work within domains and how this affects temporal dynamics of collective work have implications for the literature on crossfunctional coordination, innovation, and practice. © 2013 Academy of Management Journal.